EVALUATION OF FINANCIAL STATEMENT RECORDING IN ACCORDANCE WITH SAK ETAP AT EMPLOYEE COOPERATIVES OF THE REPUBLIC OF INDONESIA (KPRI) INSKO OFFICE OF COOPERATIVES AND SMES OF NORTH SUMATRA PROVINCE - Deasy Cahayadie Deviana; Nurlaila; Arnida Wahyuni Lubis (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study attempts to determine and evaluate SAK ETAP's suitability, as well as to identify the limitations associated with the application of SAK ETAP to the recording of financial statements at KPRI INSKO. The employed research methodology is a qualitative descriptive approach. In this study, interviews and documentation were used to collect data. This study employs a comparative qualitative descriptive method for data analysis, namely: 1) collecting data on the Financial Statements of KPRI INSKO in 2020; 2) describing, observing, comparing, and analyzing the financial statements of KPRI INSKO with SAK ETAP; and 3) drawing conclusions regarding the conformity of KPRI INSKO's financial statements with SAK ETAP. The outcomes demonstrated that KPRI INSKO's financial statements were not presented in accordance with SAK ETAP. Besides, five (5) of the fourteen (14) categories do not comply with the requirements of SAK ETAP.